Social Exclusion and Inclusion: Challenges to Orphan Care in Malawi (Nordic Journal of African Studies, 2002)
One of the major effects of the HIV/AIDS pandemic in Malawi as in sub-Saharan African in general is the rising number of orphans. Development practitioners and scholars interested in the topic argue that there is a total breakdown in family structures and social support systems. Safety nets are collapsing and increasing numbers of orphaned children are becoming destitute. This paper argues that granted the social strains caused by the effects of the HIV/AIDS pandemic, families and social support systems are developing adaptive capabilities with varying degrees of success and failure. New strategies are adopted while others are abandoned. There are many conceptions of orphanhood depending on an individual's social and economic position. The size of the family in which the orphans are found, the ages and gender of the orphaned children, the number(s) of losses of the family members, and the economic status of the care givers all have a bearing on the success or failure of the orphan care system.